Effect of low dose honey on the apoptosis and inflammation gene expression in corneal limbal stem cells and keratocytes and its efficacy as an ophthalmic formulation in the treatment of dry eye: in-vitro and clinical study - Sanie-Jahromi, Fatemeh; Khaki, Mehdi; Heydari, Mojtaba; Nowroozzadeh, Mohammad Hossein; Akbarizadeh, Amin Reza; Daneshamouz, Saeid; NejatyJahromy, Yaser; Nejabat, Maryam; Mahmoudi, Ahmad; Zareei, Athar; Nejabat, Mahmood (Frontiers in Medicine, 2024)
Background The use of honey as an eye treatment encounters challenges due to its high osmolarity, low pH, and difficulties in sterilization. This study addresses these issues by employing a low concentration of honey, focusing on both in-vitro experiments and clinical trials for treating dry eye disease in corneal cells. Methods In the in-vitro experiment, we investigated the impact of a 1% honey-supplemented medium (HSM) on limbal stem cells (LSCs) and keratocytes using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay and real-time polymerase chain reaction (PCR) for BCL-2, BAX, and IL-1β gene expression. Simultaneously, in the clinical trial, 80 participants were divided into two groups, receiving either a 1% w/v honey ophthalmic formulation or a placebo for 3 months. Study outcomes included subjective improvement in dry eye symptoms, tear break-up time (TBUT), and Schirmer’s test results. Results MTT results indicated that 1% HSM did not compromise the survival of corneal cells and significantly reduced the expression of the IL-1β gene. Additionally, participants in the honey group demonstrated a higher rate of improvement in dry eye symptoms and a significant enhancement in TBUT values at the three-month follow-up. However, there was no significant difference between the study groups in terms of Schirmer’s test values. No adverse events were observed or reported. Conclusion In conclusion, 1% honey exhibits anti-inflammatory and anti-infective properties, proving effective in ameliorating dry eye symptoms and enhancing tear film stability in patients with dry eye disease. Clinical Trial Registration: https://irct.behdasht.gov.ir/trial/63800.